Influence of tricuspid regurgitation on the prognosis of patients with cardiogenic shock - Ruka, Marinela; Schupp, Tobias; Weidner, Kathrin; Egner-Walter, Sascha; Forner, Jan; Mashayekhi, Kambis; Tajti, Péter; Ayoub, Mohamed; Akın, Muharrem; Behnes, Michael; Akın, Ibrahim; Rusnak, Jonas (Current medical research and opinion, 2024)
Tricuspid regurgitation (TR) is associated with adverse prognosis in various patient populations. However, data regarding the prognostic impact in patients with cardiogenic shock (CS) is limited. The study investigates the prognostic impact of pre-existing TR in patients with CS. Consecutive patients with CS from 2019 to 2021 were included in a monocentric registry. Every patient’s medical history, including echocardiographic data, was recorded. The influence of pre-existing TR on prognosis was investigated. Furthermore, Kaplan-Meier analyses based on TR severity were conducted. Statistical analyses comprised univariable t-test, Spearman’s correlation, Kaplan-Meier analyses, as well as multivariable Cox proportional regression models. Analyses were stratified by the underlying cause of CS such as acute myocardial infarction (AMI), or the need for mechanical ventilation. 105 patients with CS and pre-existing TR were included. In Kaplan Meier analyses, it could be demonstrated that patients with severe TR (TR III°) had the highest 30-day all-cause mortality compared to mild (TR I°) and moderate TR (TR II°) (44% vs. 52% vs. 77%; log rank p = .054). In the subgroup analyses of CS-patients without AMI, TR II°/TR III° showed a higher all-cause mortality after 30 days compared to TR I° (39% vs. 64%; log rank p = .027). In multivariable Cox regression TR II°/TR III° was associated with 30-day all-cause mortality in CS-patients without AMI (HR = 2.193; 95% CI 1.007-4.774; p = .048). No significant difference could be found in the AMI group. Furthermore, TR II°/III° was linked to an increased 30-day all-cause mortality in non-ventilated CS-patients (6% vs. 50%, log rank p = .015), which, however, could not be confirmed in multivariable Cox regression. The occurrence of pre-existing TR II°/III° was independently related with 30-day all-cause mortality in CS-patients without AMI. However, no prognostic influence was observed in CS-patients with AMI.
Gesehen am 18.11.2024